Carotid Artery Disease From Bench to Bedside and Beyond - Rezzani, Rita (IntechOpen, 2014)
This book will bring out the state of art of carotid stenosis in the basic and clinical approaches for better understanding of the mechanisms and useful therapies for these disease. We hope that would be a new current trend understanding new aspects regarding this scientific problematic involving not only anatomical, functional but also clinical questions.